Back Cover. Issue 2 (3rd July 2019) - Unknown
Abstract : The Internet of Everything, aiming to realize information exchange and communications for anything with the Internet, is experiencing tremendous growth and reaching every corner of the world. Serving as the driving force, power supply systems play a fundamental role in the development of the Internet of Everything. Thereafter, in this review, some critical challenges and advances as well as some promising directions for both power supply systems and their units to meet the requirements for the development of the Internet of Everything are highlighted.